PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 22 DURI BARAT KABUPATEN BENGKALIS - Afriyenti '; Hendri Marhadi; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the lack of student learning outcomes IPS, it can be seen from the results of social research Elementary School fourth grade students 22 Duri West, with the average value of class 67.50, therefore, the researchers gave the study an alternative to the implementation of cooperative learning model type TGT in the fourth grade elementary school 22 Duri Barat. This study aims to improve learning outcomes IPS Elementary School fourth grade students 22 Duri Barat for the Application of Cooperative Learning Model Teams Games Toirnament (TGT). Design research is action research (PTK) with two cycles .. Based on the analysis of research data after applying cooperative learning model Teams Games Toirnament (TGT) the average percentage of teachers in the first cycle of activity increased 79.17% to 91, 66% in the second cycle , The average percentage of student activity also increased, which is 75% in the first cycle increased to 83.91% in the second cycle. learning outcomes in basic score with the average value of 67.50 and the first cycle of students increased by an average value of 69.58 with classroom learning outcomes percentage increases by 2.98% and the percentage of students who completed 66.66%, and the cycle II increases again with an average of 78.12 with the percentage improvement class learning outcomes 13.59% and the percentage of students who completed 83.33%. These results indicate that the application of cooperative learning model type Teams Games Toirnament (TGT), can improve learning outcomes IPS Elementary School fourth grade students 22 Saber Duri Barat. Key Words: Teams Games Tornament,  Learning Outcomes IPS